'In the Islands people don't really talk about this stuff, so you go through life on your own': An arts-based study exploring intimate relationships with young people in Samoa. Issue 5 (4th May 2019) - Heard, Emma; Fitzgerald, Lisa; Va'ai, Sina; Collins, Fiona; Whittaker, Maxine; Mutch, Allyson
Abstract: This study explores conceptualisations and understandings of intimate relationships with young people in Samoa – an at-risk group experiencing high rates of intimate partner violence and alienation from sexual and relationship health promotion. Insights contribute to the immediate need to advance knowledge and practice around prevention with this group. An arts-based approach, which included a two-day interactive drama workshop coupled with follow-up, peer-led focus groups, was used to explore perceptions and understandings related to intimate relationships with 15 tertiary educated young people (nine female and six male) from across Samoa. Intersectionality informed the data collection and thematic analysis, examining participants' lived experiences and the ways multiple and intersecting identities interact within social and cultural systems to influence and inform these experiences. Outcomes highlight important tensions for young people, including the way in which age, gender, religion and sexuality interact with social hierarchies and power structures, socially prescribed gender norms, family structures and globalisation. This research provides insights that can inform the development of prevention strategies to address the root causes of intimate partner violence, building the knowledge and skills required for establishing intimate relationships free from violence with young people.